Pendidikan Akhlak Perspektif Ibnu Miskawaih Dan Relevansinya Dalam Pendidikan Islam Kontemporer - Mutiara; Ali Maulida (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study aims to examine Ibn Miskawayh’s concept of moral education and its relevance to contemporary Islamic education. The study is motivated by the moral crisis in modern education, reflected in the decline of honesty, responsibility, and social awareness, which highlights the need to strengthen education that balances intellectual, spiritual, and moral dimensions. This research employed a qualitative approach with a library research design. Data were collected from relevant academic literature and analyzed descriptively through content analysis. The findings reveal that, according to Ibn Miskawayh, moral education is the core of education, aiming to shape the human soul toward goodness and happiness. Morality, in his view, can be developed through habituation, supervision, discipline, role modeling, early childhood education, and the strengthening of spiritual values. His thought also emphasizes the balance of reason, anger, and desire as the foundation for forming a virtuous personality. In the context of contemporary Islamic education, Ibn Miskawayh’s ideas remain relevant to character education, the integration of moral values into learning, the development of an Islamic school culture, and the synergy between family and school. This study concludes that Ibn Miskawayh’s thought can serve as a conceptual foundation for developing moral education that is more integrative, contextual, and oriented toward producing individuals who are intellectually capable and morally virtuous.